Eläinlääkärit 2007 - Venäläinen, Anita (Helsinki : Elintarviketurvallisuusvirasto Evira, 2007)
Resumé: Veterinärer 2007.
Abstract: Veterinarians 2007.
Keywords: eläinlääkärit; luettelot; hakemistot; henkilöhakemistot